Assessing legacy contaminants in sediments from marine protected areas of the central coast of São Paulo (Brazil) (Brazilian Journal of Oceanography, 2017)
The presence of legacy contaminants in sediments from three Marine Protected Areas (MPAs) of the coast of São Paulo State was evaluated. Four sampling surveys were conducted between 2013 and 2015 in 10 sites, distributed along the Laje de Santos Marine and Xixova-Japui State Parks (PEMLS and XJSP, respectively) and Central Coast Marine Protection Area (APAMLC). Samples were analyzed for sediment texture, total organic carbon, CaCO3, metals (Al, Fe, Hg, Cd, Co, Cr, Cu, Ni, Pb and Zn), aliphatic and polycyclic aromatic hydrocarbons (AH and PAH). Sediments were generally sandy (excepting muddy samples from APAMLC), with variable amounts of TOC, OM and CaCO3. Most of the sediments exhibited low to moderate concentrations of metals, except APAMLC. Low contamination of sediments by hydrocarbons was found but samples from XLSP and APAMLC exhibited the highest concentrations of biogenic AH and PAH from pyrogenic sources. In APAMLC and PEMLS, the levels of metals can be considered as background levels according to geochemical indices (Igeo and EF). In XJSP and especially in APAMLC data indicated poor sediment quality, probably due to the effect of anthropic activities.